2014
DOI: 10.1016/j.jep.2014.05.059
|View full text |Cite
|
Sign up to set email alerts
|

Some Nigerian anti-tuberculosis ethnomedicines: A preliminary efficacy assessment

Abstract: Ethnopharmacological significance Nigerian herbalists possess indigenous ethnomedicinal recipes for the management of tuberculosis and related ailments. Aim of the study To carry out a collaborative preliminary modern scientific evaluation of the efficacy of some Nigerian ethnomedicines used by traditional medicine practitioners (TMPs) in the management of tuberculosis and related ailments Materials and methods Ethnomedicinal recipes (ETMs) were collected from TMPs from locations in various ecological zone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…Due to increase in multi drug resistance (MDR) and extensively drug resistance TB (XDR) strains of M. tuberculosis, the need of discovering newer anti-mycobacterial agents to eradicate the infections has increased. A study by Ibekwe et al, [15] showed that Pterocarpus osun Craib exhibited an MIC value of 1225 μg/ml against strain H37.…”
Section: Discussionmentioning
confidence: 99%
“…Due to increase in multi drug resistance (MDR) and extensively drug resistance TB (XDR) strains of M. tuberculosis, the need of discovering newer anti-mycobacterial agents to eradicate the infections has increased. A study by Ibekwe et al, [15] showed that Pterocarpus osun Craib exhibited an MIC value of 1225 μg/ml against strain H37.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the use of Psidium guajava for the treatment of cough has been documented in Pakistan [63], Uganda [64,65], South Africa [27], and Zimbabwe [66]. On the other hand, Garcina kola has been extensively documented as a cough remedy in Nigeria [29,36,49] but no record has been found in other parts of the world. Furthermore, reports of the use of approximately 32% of the plants such as Corchorus olitorius, Hybanthus enneaspermus and Theobroma cacao as cough remedy in folk medicine were not found ( Table 2).…”
Section: Diversity and Ethnobotanical Indices Of Plant Species Used Amentioning
confidence: 99%
“…Awomukwu et al, [81] investigated the presence of alkaloids, flavonoids, saponins, tannins and little amount of phenols on stem, pod and root extract of C. sieberiana and reported the antiulcer, antidiarrhoeal, antimalarial, antitrypanosomal and other pharmacological activities. Reference [82] reported the antimycobacterium activity of C. sieberiana.…”
Section: Pharmacological Activities Of Nigerian Medicinal Plantsmentioning
confidence: 99%